Decreased ultrasound echogenicity as a thyroid hypofunction marker and correlation with autoantibody levels - Dimić, Dragan; Velojić Golubović, Milena; Radenković, Saša; Radojković, Danijela; Pešić, Milica (Vojnosanitetski pregled, 2020)
Background/Aim. The value of ultrasound in functional disorders can be significant. That is why the question arises on the use of ultrasound examination of thyroid gland and its echogenicity as a screening method in early detection of disfunctions, of the gland primarily subclinical and clinical forms of hypothyreoidism. The objective of this paper was to determine antibodies of thyroid peroxidase (anti-TPO) and thyroglobuline antibodies (anti-TG) increase frequency in relation to the character of ultrasound echogenicity as well as to estimate the frequency of subclinically and clinically obvious hypothyreoidism in relation to the changed echogenicity. Methods. Study included 656 patients in outpatient clinic during 2014. All examinees underwent ultrasound examination of thyroid gland, the blood was taken for determination of free thyroxine (FT4), thyroid-stimulating hormone (TSH), anti-TPO and anti-TG. The patients were divided into two groups; the group A with normal echogenicity of thyroid gland tissue, and the group B with decreased echogenicity. The group B was divided into two subgroups, B1 with a mildly decreased and B2 with significantly decreased echogenicity. Results. TPO antibody, TSH and TG antibody positivity and their mean values in the group B were significantly higher, as well as in subgroups B1 and B2, in relation to the group A (p < 0.001). In the group A, only 4 (1%) examinees were indicated with subclinical hypothyreoidism. In the group B, the sublinical hypothyreoidism was indicated in 42, while the clinical hypothyreoidism was indicated in 16 examinees. Fifty-eight (25%) examinees suffered from thyroid gland altered function. In the subgroup B1, 16 examinees were indicated with subclinical and 4 with clinical hypothyreoidism. Twenty (11%) examinees suffered from altered thyroid function. In the group B2, the subclinical hypothyreoidism was found in 26 examinees, while the clinical hypothyreoidism was found in 12. Thirty-eight (76%) examinees suffered from altered thyroid function. Conclusion. The ultrasound screening of thyroid gland plays an important role in early detection of thyroid disfunction, i.e., sublinical and clinical hypothyreoidism. Decreased ultrasound echogenicity represents the significant marker of altered thyroid gland function. In these persons we have determined the high percentage of subclinical and clinical hypothyreoidism frequency.